THE PROBLEMS OF DETERMINATION OF ABUNDANCES IN ATMOSPHERES OF K GIANT STARS - Komarov, N. S.; Basak, N. Yu.; Gorbaneva, T. I.; Golubovsky, V. V.; Kantsen, L. E.; Shevchuk, T. V. (Одеські астрономічні публікації, 2017)
The influence of effective temperatures of surface gravities, of metallicities, of microturbulent velocities as well as of effects non-LTE, of starspotting, of chromospbere, corona and wind of different nonthermal mechanisms on determination of abundances in atmospheres of cool stars have been discussed briefly.